2003
DOI: 10.1034/j.1600-0463.2003.1110504.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple co‐infections (Mycoplasma, Chlamydia, human herpes virus‐6) in blood of chronic fatigue syndrome patients: association with signs and symptoms

Abstract: Previously we and others found that a majority of chronic fatigue syndrome (CFS) patients showed evidence of systemic mycoplasmal infections, and their blood tested positive using a polymerase chain reaction assay for at least one of the four following Mycoplasma species: M. fermentans, M. hominis, M. pneumoniae or M. penetrans. Consistent with previous results, patients in the current study (n=200) showed a high prevalence (overall 52%) of mycoplasmal infections. Using forensic polymerase chain reaction we al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 37 publications
(89 reference statements)
4
76
0
4
Order By: Relevance
“…In addition to Mycoplasma species (OR=13.8, CI 95% 5.8-32.9, p<0.001), co-infections with C. pneumoniae (OR=8.6, CI 95% 1.0-71.1, p<0.01) and HHV-6 (OR=4.5, CI 95% 2.0-10.2, p<0.001) were also found [197]. The presence of these infections was also related to the number and severity of signs and symptoms [201]. Similarly, Vojdani et al also found Mycoplasma species in a majority of CFS/ME patients [200], but this has not been seen in all studies [202].…”
Section: Chronic Fatigue Syndrome (Cfs)mentioning
confidence: 67%
“…In addition to Mycoplasma species (OR=13.8, CI 95% 5.8-32.9, p<0.001), co-infections with C. pneumoniae (OR=8.6, CI 95% 1.0-71.1, p<0.01) and HHV-6 (OR=4.5, CI 95% 2.0-10.2, p<0.001) were also found [197]. The presence of these infections was also related to the number and severity of signs and symptoms [201]. Similarly, Vojdani et al also found Mycoplasma species in a majority of CFS/ME patients [200], but this has not been seen in all studies [202].…”
Section: Chronic Fatigue Syndrome (Cfs)mentioning
confidence: 67%
“…Since we had studied the signs and symptoms in over a thousand Gulf War veterans, we were struck by the similarity of their illnesses to Chronic Fatigue Syndrome and Fibromyalgia Syndrome found in civilians. Studying these civilian illnesses we found similar chronic infections but in the case of civilians there were multiple infections (Nicolson et al, 2003a). We have been working on new therapeutic approaches to treat these illnesses, and one of my recent efforts has been directed at repair of their intracellular membranes, which we have found are damaged and leaky in these illnesses.…”
Section: Permit Me To Go Back To the 1972 Publication By Singer Andmentioning
confidence: 89%
“…Recently, Eskow et al (37) Other studies have shown that a high proportion of patients with chronic fatigue present infection by at least one species of Mycoplasma: M. hominis, M. pneumoniae and M. fermentans (28,33). It was also reported that patients with chronic fatigue demonstrated evidence of infection by C. pneumoniae and active human herpes virus-6 (28).…”
Section: Is Lyme Disease-like Syndrome a New Tick-borne Disease?mentioning
confidence: 99%
“…The inability of the host organism to completely eliminate the pathogen leads to a chronic infection state, which can cause tissue damage sequelae. Thus, the infection, dissemination and development of immunity against Chlamydophila pneumoniae seem to have an important role in several diseases such as reactive arthritis, atherosclerosis, Alzheimer disease, and multiple sclerosis (28,29). A possible role of coinfection by M. pneumoniae and C. pneumoniae has been associated with the progress of atherosclerosis (29).…”
Section: Is Lyme Disease-like Syndrome a New Tick-borne Disease?mentioning
confidence: 99%
See 1 more Smart Citation